Pengaruh Penambahan Kitosan dan Selulosa Terhadap Performa Bioplastik Berbahan Baku Pati Singkong Karet - Andini Puspita Dewi; Rintis Manfaati; Unung Leoanggraini; Aqqilla Mardhiyana (Fluida, 2023)
Manihot Glaziovii has a starch content of 77.87 making it potential to be used as raw material for bioplastics manufacturing as a substitute for conventional plastics. It requires the addition of biopolymers (fillers) and plasticizers to overcome weaknesses against mechanical properties and water resistance. This study aims to determine the effect of filler variations on the quality of bioplastics to be compared with SNI No.7188.7:2016 using fillers addition in the form of chitosan and cellulose from newsprint and sorbitol as plasticizer were expected to improve the quality of the bioplastics. Melt intercalation method are used with heating temperature of 60Â°C-80Â°C for 60 minutes and stirring speed of 500 rpm. The variation of cellulose combination for 30% chitosan (w/w starch) was 10%, 12%, 14%, 16%, and 18% while the variation of chitosan for 16% cellulose (w/w starch) was 20%, 30%, 40 %, 50%, and 60%. Based on the test results, the best characteristic value for the water absorption is 120.65%, biodegradability is 32.74%, tensile strength value is 15.72 MPa, WVTR value is 6.52 g/m2.hour, and elongation is 29.76%. From the test results, it can be concluded that bioplastics made from Manihot Glaziovii starch have not been able to meet SNI No.7188:2016.